105k views
4 votes
Hi are you able to solve it by using a step called exponential equations?

Hi are you able to solve it by using a step called exponential equations?-example-1

1 Answer

4 votes

Given the equation:


6^(2-3x)=6^(-2x-2)

since both bases are 6, we can equate both exponents to get the following equation:


2-3x=-2x-2

solving for x, we get:


\begin{gathered} 2-3x=-2x-2 \\ \Rightarrow-3x+2x=-2-2=-4 \\ \Rightarrow-x=-4 \\ \Rightarrow x=4 \end{gathered}

therefore, the solution of the equation is x = 4

User Gebezs
by
5.6k points